Bedside evaluation of swallowing function to predict aspiration pneumonia in Duchenne muscular dystrophy. Issue 2 (April 2023) - Kawamoto-Hirano, Ai; Ikeda, Ryoukichi; Takahashi, Toshiaki; Taniguchi, Sayaka; Yoshioka, Masaru; Tanaka, Hiroyasu; Oizumi, Hideki; Totsune, Tomoko; Oshiro, Saki; Baba, Toru; Takeda, Atsushi; Kobayashi, Yuta; et al.
Abstract: Objective: Aspiration pneumonia is one of the leading causes of death in patients with muscular dystrophy; therefore, it is important to predict its occurrence in the clincal setting. We aimed to examine the usefulness of repeated saliva swallowing test (RSST), modified water swallowing test (MWST), and flexible endoscopic evaluation of swallowing (FEES) for evaluating the Hyodo score at the bedside, to predict the risk of aspiration pneumonia in patients with Duchenne muscular dystrophy (DMD). Methods: In this retrospective cohort study involving 43 patients, we evaluated the swallowing function using the RSST, MWST, and FEES, and predicted the likelihood of aspiration pneumonia within 2 years after the assessment. The Hyodo score, a scoring system for evaluating the swallowing function determined by the FEES, was used. Results: Pneumonia was observed in 14 patients (32.6%). The RSST was not significantly useful for predicting the onset of pneumonia. The MWST was reported to have a cutoff value of < 4 points. Significantly more patients in the pneumonia group had an MWST score of < 4 points. The results revealed that the occurrence of pneumonia could be predicted based on a Hyodo cutoff score of ≥ 6. Significantly more patients in the pneumonia group had an MWST score of < 4 or a Hyodo score of ≥ 6. Conclusions: Combining MWST and FEES is useful for evaluating the bedside swallowing function and predicting the onset of pneumonia.